Prediction of all-cause and cardiovascular mortality using central hemodynamic indices among elderly people: systematic review and meta-analysis - Vieceli, Tarsila; Brambilla, Bárbara; Pereira, Raphael Quintana; Dellamea, Bruno Schmidt; Stein, Airton Tetelbom; Grezzana, Guilherme Brasil (São Paulo Medical Journal, 2021)
BACKGROUND: Despite widespread usage of central blood pressure assessment its predictive value among elderly people remains unclear. OBJECTIVE: To ascertain the capacity of central hemodynamic indices for predicting future all-cause and cardiovascular hard outcomes among elderly people. DESIGN AND SETTING: Systematic review and meta-analysis developed at the Del Cuore cardiology clinic, in Antonio Prado, Rio Grande do Sul, Brazil. METHODS: 312 full-text articles were analyzed, from which 35 studies were included for systematic review. The studies included needed to report at least one central hemodynamic index among patients aged 60 years or over. RESULTS: For all-cause mortality, aortic pulse wave velocity (aPWV) and central systolic blood pressure (SBP) were significant, respectively with standardized mean difference (SMD) 0.85 (95% confidence interval, CI 0.69-1.01; I2 96%; P < 0.001); and SMD 0.27 (95% CI 0.15-0.39; I2 77%; P 0.012). For cardiovascular mortality brachial-ankle PWV (baPWV), central SBP and carotid-femoral PWV (cfPWV) were significant, respectively SMD 0.67 (95% CI 0.40-0.93; I2 0%; P 0.610); SMD 0.65 (95% CI 0.48- 0.82; I2 80%; P 0.023); and SMD 0.51 (95% CI 0.32-0.69; I2 85%; P 0.010). CONCLUSIONS: The meta-analysis results showed that aPWV was promising for predicting all-cause mortality, while baPWV and central SBP demonstrated consistent results in evaluating cardiovascular mortality outcomes. Thus, the findings support usage of central blood pressure as a risk predictor for hard outcomes among elderly people. REGISTRATION NUMBER IN PROSPERO: RD42018085264